If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying l + l + 4 = 100 Reorder the terms: 4 + l + l = 100 Combine like terms: l + l = 2l 4 + 2l = 100 Solving 4 + 2l = 100 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2l = 100 + -4 Combine like terms: 4 + -4 = 0 0 + 2l = 100 + -4 2l = 100 + -4 Combine like terms: 100 + -4 = 96 2l = 96 Divide each side by '2'. l = 48 Simplifying l = 48
| (3x+7)/4+(x+53)/7=12 | | .09x+.25(10-x)=.15(10) | | 3a^2=192 | | -16(3t+-4)+55=0 | | 2(x-8)=3x+3 | | 9x-2x-28=14 | | -4(t-5)+8t=9t-9 | | 28/16=x-8/20 | | D/30+1=4 | | 7b-4=-9 | | -2x+3= | | 25=5q-50 | | 4xy^2-8= | | 2t=3t+1 | | 62=3c+8 | | d-257x=8328 | | 3r^2-3r-15= | | x/6-18=0 | | (x^2)-4x-32= | | 3a+7=4a+9 | | 11x-(7x-2)=10 | | (5a+6)=2(3a+8) | | 5x^2-25x=30 | | x^2+25x-224=0 | | 12cos(x)-6=0 | | -39=-6+3(x-3) | | 14+3n=7b-7.4 | | (-3/4x+24)+2=-1/x+6 | | 450-3x=300 | | -2x+6=-8 | | 2t-3(6-t)=7-(-11) | | k.5-6=2 |